"Obubomi Bulukhuni/It is a Hard Life, This": Journeys in and narratives of childhood cancer in a South African public healthcare context - Riekert, Yolande (Social Anthropology, 2015)
This research examines the ways in which a history of social segregation together with present actions by the state interact to inform the nature of healthcare narratives of mothers and children in the case of a childhood cancer diagnosis. I argue that families become internally displaced to seek life-saving treatment for the child diagnosed with cancer. By actively engaging with theories of ‘home’ and ‘households’ I aim to present greater insights into the ways in which people create meanings for these terms in the hospital setting. I argue that my participants come to share many of the characteristics of internally displaced people, due to the inequality that manifests in the healthcare system.